Cardiovascular Imaging and Image Analysis - El-Baz, Ayman; Suri, Jasjit S.; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
This book covers the state-of-the-art approaches for automated non-invasive systems for early cardiovascular disease diagnosis. It includes several prominent imaging modalities such as MRI, CT, and PET technologies. There is a special emphasis placed on automated imaging analysis techniques, which are important to biomedical imaging analysis of the cardiovascular system. Novel 4D based approach is a unique characteristic of this product. This is a comprehensive multi-contributed reference work that will detail the latest developments in spatial, temporal, and functional cardiac imaging. The main aim of this book is to help advance scientific research within the broad field of early detection of cardiovascular disease. This book focuses on major trends and challenges in this area, and it presents work aimed to identify new techniques and their use in biomedical image analysis.
A Novel 4D PDE-Based Approach for Accurate Assessment of Myocardium Function Using Cine Cardiac Magnetic Resonance Images. Magnetic Resonance Imaging Evaluation of Left Ventricular Dimentions and Function of Pericardial and Myocardial Disease. Improving Full-Cardiach Cycle Strain Estimation from Tagged CMR by Accurate Modeling of 4D & #D image Appearance Characteriistics. New Automated Markov-Gibbs Random Field Based Framework for Myocardial Wall Viability Quantification on Agent Enhanced Cardiac Magentic Resonance Images. Accurate Automatic Analysis of Cardiac Cine Images. Segmentation of the Left Ventricle from Cardiac MR Images Based on Radial GVF Snake. 4D Deformable Models with Temporal Constraints: Application to 4D Cardiac Image Segmentation. Multistage Hybrid Active Apperance Model Matching: Segmentation of Left and Right Ventricles in Cardiac MR Images. Automatic Detection of Left Ventricle in 4D MR Images. Fully Automated Framework for the Analysis of Myocardial First-Pass Perfusion MR Images. First-Pass Myocardial Perfusion Cardiovascular Magnetic Resonance at 3 Tesla. Quantitative Analysis of First-Pass Contrast-Enhanced Myocardial Perfusion MRI. Unsurpassed Inline Analysis of Cardiac Perfusion MRI. Model-Based Registration for Dynamic Cardiac Perfusion MRI.Improved Semi-Automated Segmentation of Cardiac CT and MR Images.
Includes bibliographical references and index.
Also available in print format.
Keywords: Cardiovascular system -- Diseases -- Diagnosis; Diagnostic imaging; MEDICAL / Cardiology; TECHNOLOGY & ENGINEERING / Biomedical; Automated Imaging Techniques; Cardiac CT and MR Imaging; Magnetic Resonance Imaging; Medical Image Segmentation; Myocardial Infraction; 4D Imaging of the Cardiovascular System; Electronic books